Transferable Emissions Permits - Tian, Gangxing (Université d'Ottawa | University of Ottawa, 2001)
This paper introduces the rationale of transferable emissions permits as an instrument in pollution control policies and the applicability of this instrument. Then the issues in implementation of emissions permits system are discussed. The experience of t